Playwrights for Tomorrow : A Collection of Plays, Volume 11 - Ballet, Arthur H. (Book collections on Project MUSE., 2014)
Playwrights for Tomorrow was first published in 1973. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. This volume presents four plays by writers who have worked under the program of the Office for Advanced Drama Research (O.A.D.R.) at the University of Minnesota, an experimental project which provides promising playwrights with the opportunity of working with cooperating theatres in the production of their plays. Arthur H. Ballet, the editor, is director of the O.A.D.R. The plays in this volume and the theatres which cooperated in their production are Boxes by Susan Yankowitz, Magic Theatre, Berkeley, California; Canvas by David Roszkowski, Scorpio Rising Theatre, Los Angeles; Bierce Takes on the Railroad! by Philip A. Bosakowski, Theatre III, College of Marin, Kentfield, California; and Chamber Piece by John O'Keefe, Magic Theatre, Berkeley, California. In an introduction Professor Ballet discussed the program and accomplishments of the O. A.D.R., which was established with the aid of a Rockefeller Foundation grant. He writes: "It seemed obvious that no artist worked in more lonely isolation and needed more direct contact with the theatre than the playwright. Despite loud pronouncements . . . that theatres outside of New York were searching for new plays and writers, the evidence indicates that very few theatres really wanted to work with unknown but living playwrights. The O.A.D.R., in its small way, has tried to open a highway . . . between new, often untried writers and willing, even brave theatres. As Speech and Drama (England) pointed out in a review of earlier volumes of the Playwrights for Tomorrow series: "Schemes like this one at Minnesota deserve the highest praise. On the evidence of these volumes, the executive committee which operates this venture is not attempting to impose any single imprint on its authors--a further example of the generosity of the patronage."